Effects of partially dismantling the CD4 binding site glycan fence of HIV-1 envelope glycoprotein trimers on neutralizing antibody induction - Crooks, Ema T; Osawa, Keiko; Tong, Tommy Yuh Koon *; Grimley, Samantha L; Dai, Yang D; Whalen, Robert G; Kulp, Daniel W; Menis, Sergey; Schief, William R; Binley, James M (Elsevier, 2017)
Previously, VLPs bearing JR-FL strain HIV-1 Envelope trimers elicited potent neutralizing antibodies (nAbs) in 2/8 rabbits PLoS Pathog 11(5): e1004932) by taking advantage of a naturally absent glycan at position 197 that borders the CD4 binding site (CD4bs). In new immunizations, we attempted to improve nAb responses by removing the N362 glycan that also lines the CD4bs. All 4 rabbits developed nAbs. One targeted the N197 glycan hole like our previous sera. Two sera depended on the N463 glycan, again suggesting CD4bs overlap. Heterologous boosts appeared to reduce nAb clashes with the N362 glycan. The fourth serum targeted a N362 glycan-sensitive epitope. VLP manufacture challenges prevented us from immunizing larger rabbit numbers to empower a robust statistical analysis. Nevertheless, trends suggest that targeted glycan removal may improve nAb induction by exposing new epitopes and that it may be possible to modify nAb speciUcity using rational heterologous boosts.